Prevalência de osteoporose em pacientes com doença pulmonar obstrutiva crônica no Brasil: uma revisão de literatura - LEDA, Talíbio de Arruda (2023)
Chronic Obstructive Pulmonary Disease (COPD) is a respiratory problem characterized by chronic and progressive airflow obstruction. This limitation is caused by the association of small airway disease (chronic obstructive bronchitis) and parenchymal destruction (emphysema). COPD often has concomitant chronic diseases, such as osteoporosis. This is a chronic disease characterized by low bone mass and microarchitectural deterioration of bone tissue, leading to fragility and fractures. The etiology of osteoporosis is complex and may be a consequence of chronic inflammatory lung disease, the therapy used in the disease, and natural changes due to aging. This study aims to carry out a theoretical survey of the available scientific literature regarding the prevalence of osteoporosis in patients with COPD in Brazil. An integrative literature review was carried out in the Pubmed and SciELO databases, from January to March of 2022, using articles in English and Portuguese, so that the selected articles were those that showed the prevalence of osteoporosis in patients with COPD in Brazil. After data collection, an assessment of the prevalence found was carried out and compared with the world literature. The initial search included 505 studies, 08 of which met the criteria established for this review. The global prevalence of osteoporosis found in patients with COPD was 41.6%, similar to that found in previous systematic reviews. This prevalence was substantially higher than that found in control groups, composed of healthy individuals. Osteoporosis in COPD deserves great interest and concern from the scientific community, since the loss of bone mass increases the risk of fractures, contributing to the individual's loss of functionality and also to the worsening of the pulmonary functional capacity of the patient with COPD. It was concluded, therefore, that the presence of COPD can increase the risk of the individual developing osteoporosis, a comorbidity that is often neglected in these cases. Thus, greater awareness is highly needed to diagnose osteoporosis at an early stage, and practitioners should be aware of the risk of this pathology in this patient population.